PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, TARIF PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM (Studi Pada Wajib Pajak Orang Pribadi Yang Terdaftar di KPP Pratama Malang Selatan) - Evi Rahmawati Lazuardini; Jeni Susyanti; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purposes of this research are: 1) To analyze the effect of understanding tax regulations on taxpayer compliance Micro, Small and Medium Enterprises (MSMEs). 2) To analyze the effect of tax rate on taxpayer compliance of Micro, Small and Medium Enterprises (MSMEs). 3) To analyze the effect of tax sanctions on taxpayer compliance of Micro, Small and Medium Enterprises (MSMEs). This research uses quantitative research method by using survey research form. The sample of this research is 100 respondents taken by using Purposive Sampling method.The results of this study show that: 1) The understanding of tax laws has a positive and significant impact on compliance of MSMEs taxpayers. 2) The tax rate has a positive and significant effect on the compliance of the MSMEs taxpayer, and 3) Tax sanction has negative and insignificant effect on taxpayer compliance of MSMEs. This result indicates that taxpayer compliance of individuals registered in KPP Pratama Malang Selatan is not affected by tax sanction. Keywords: taxpayer compliance, understanding tax laws, tax rates, and tax sanctions